2022
DOI: 10.1021/acsanm.2c03274
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Opal Photonic Nanostructures for Enhanced Light Harvesting in CH3NH3PbI3 Perovskite Solar Cells

Abstract: Light management strategies using photonic crystals have been proven to efficiently improve light harvesting and subsequently conversion efficiency of various optoelectronic devices. This study focuses on 3D inverse opal CH 3 NH 3 PbI 3 photoanodes in perovskite solar cells from a combined numerical and experimental approach. Varying the pore size and the layer thickness in numerical simulations, we first determined theoretical optimum from a purely optical point of view. Corresponding 3D inverse opal photonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Daem et al theoretically simulated the optimum pore size of a 3D inverse opal (3D-IO) photonic nanostructuration through a home-made genetic algorithm (GA) and a coupled-wave analysis (RCWA), and could experimentally demonstrated that the MAPbI 3 -PS500 3D-IO photonic nanostructuration with 500-nm-diameter spherical pores obtained optimal light absorption. 98…”
Section: D Pcmentioning
confidence: 99%
“…Daem et al theoretically simulated the optimum pore size of a 3D inverse opal (3D-IO) photonic nanostructuration through a home-made genetic algorithm (GA) and a coupled-wave analysis (RCWA), and could experimentally demonstrated that the MAPbI 3 -PS500 3D-IO photonic nanostructuration with 500-nm-diameter spherical pores obtained optimal light absorption. 98…”
Section: D Pcmentioning
confidence: 99%
“…The refractive index of PC varies periodically, endowing them with special optical properties of photonic stopband, which indicates that the light at a certain wavelength cannot transmit the materials and will be reflected. The photonic stopband character renders PC to be used in various fields, such as catalyst [3,4], solar cells [5,6], anti-counterfeiting [7,8] and sensing [9][10][11][12][13]. Among these applications, the PC-based sensing for external stimuli such as temperature [14,15], humidity [16], strain [17], and chemical [18][19][20][21][22][23] and biological [10,13,[24][25][26][27] molecules have been paid more attention due to their regulable optical performance, for example using fluorescence enhancement effect [20,21], changeable photonic stopband position [22,23] or Debye diffraction effect [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Some porous particles also display improved compaction ability during tablet manufacturing [4]. Porous particles have been reported in the literature for both active pharmaceutical ingredients (API) [5][6][7] and excipients [2][3][4], in addition to many other fields in materials science, such as electrocatalysis [8][9][10][11], gas sensing [12] and other applications [9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This sacrifi-cial templating approach has been much studied for the preparation of metal oxides or silica with controlled porosity using a polymer template removed by heat treatment [22][23][24][25][26][27][28]. Polystyrene beads are one of the most common sacrificial templates because their diameter can be controlled during the synthesis allowing a broad range of pore sizes [13][14][15][27][28][29].…”
Section: Introductionmentioning
confidence: 99%